Polyphenol content, profile, and distribution in old, traditional apple varieties - Jakobek Barron, Lidija; Ištuk, Jozo; Buljeta, Ivana; Voća, Sandra; Šic Žlabur, Jana; Lesičar, Jasmin; Skendrović Babojelić, Martina (2020)
Apples are an important source of polyphenols in the human diet. They have also shown many potentially beneficial effects on human health. Old, traditional apple varieties grown in the past could also be valuable varieties but little is known about their polyphenolic compounds and characteristics in general. The aim of this study was to collect 25 old, traditional apple varieties, to determine their polyphenolic profile and the amounts of total polyphenols in the peel and flesh, and to compare them with a commercial variety. To the best of our knowledge, some of those varieties have never been studied before (‘Mašanka’, ‘Bobovac’, ‘Batulenka’, ‘Krastavka’). Total polyphenols were determined by using the Folin-Ciocalteu method and individual polyphenol identification was done by using an RP-HPLC. The flesh contained 170 to 941 mg kg-1 fresh weight (FW) of total polyphenols, and the peel contained 931 to 3791 mg kg-1 FW. In comparison to the commercial variety, the peel of all old varieties had higher polyphenol content, while the flesh of only some old varieties was richer in polyphenols. Principal component analysis showed possible clustering. Eighteen individual polyphenols were distributed in apple peel and flesh. The dominant polyphenol subgroups in the peel were flavonols (18 to 80 %) and flavan-3-ols (6 to 66 %), and in the flesh those subgroups were phenolic acids (41 to 85 %) and flavan-3-ols (3-49 %).
Bibliografija: str. 116-117.
Summary.
Keywords: Jabuka -- Polifenoli -- Flavonoli -- Antocijani -- Sorte jabuka -- Tradicionalne sorte -- Kardiovaskularno zdravlje; Hrvatska